2004
DOI: 10.1172/jci20986
|View full text |Cite
|
Sign up to set email alerts
|

Central role of the P2Y12 receptor in platelet activation

Abstract: Platelet activation occurs in response to vessel injury and is important for the arrest of bleeding. Platelet activation during disease states leads to vascular occlusion and ischemic damage. The P2Y 12 receptor, activated by ADP, plays a central role in platelet activation and is the target of P2Y 12 receptor antagonists that have proven therapeutic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
286
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(301 citation statements)
references
References 53 publications
6
286
1
3
Order By: Relevance
“…ADP is a very important molecule in platelet activation through the purogenic receptor P2Y12 [Dorsam and Kunapuli, 2004]. It is known that activated platelets play a critical role in vasculogensis [Daub et al, 2006; Leshem‐Lev et al, 2010] and that the second day after BMP2 induction is a critical time for the formation of new vessels to carry osteoprogenitors from the nerve to the site of bone formation [Dilling et al, 2010; Lazard et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…ADP is a very important molecule in platelet activation through the purogenic receptor P2Y12 [Dorsam and Kunapuli, 2004]. It is known that activated platelets play a critical role in vasculogensis [Daub et al, 2006; Leshem‐Lev et al, 2010] and that the second day after BMP2 induction is a critical time for the formation of new vessels to carry osteoprogenitors from the nerve to the site of bone formation [Dilling et al, 2010; Lazard et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The activated platelets generate a rapid response including secretion of ADP from the dense granules, resulting in the formation of stable thrombus through GPIIb/IIIa-fibrinogen binding [8,13]. ADP affects platelet via P2Y receptors [5,8,9], and p44/p42 MAP kinase is established as an intracellular downstream effector of P2Y receptors in platelet aggregation [7]. Therefore, our present results strongly suggest that raloxifene could upregulate the sensitivity of p44/p42 MAP kinase in response to ADP released during shear stress, resulting in platelet hyperaggregation in the clinical dosage of raloxifene.…”
Section: Discussionmentioning
confidence: 99%
“…p44/p42 mitogen-activated protein (MAP) kinase is reportedly activated by ADP through both P2Y1 and P2Y12 receptors, resulting in thromboxane A 2 generation in platelets [7]. A recent investigation revealed that P2Y12 receptor is principal for mediating ADP-induced platelet aggregation and the thromboembolism [8,9]. We have reported that P2Y12 receptor plays an important role in the spontaneous microaggregation induced by shear stress in patients with diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Activated platelets release thromboxane A2 and ADP, which is stored in and secreted from dense granules in platelets, amplifying also the response to other agonists. The P2Y 12 receptor plays a central role in platelet activation amplification and the ADP-P2Y 12 interaction is crucial for stable, platelet-rich thrombus generation at the site of the vessel wall injury [2]. In an in vivo mesenteric artery injury model, the time for the appearance of the first thrombus was prolonged and only small, unstable thrombi formed in P2Y 12 -/- mice without reaching an occlusive size.…”
Section: Platelets: Their Central Role In Acs/pcimentioning
confidence: 99%
“…Attenuation of platelet aggregation induced by several agonists, modulation of platelet procoagulant activity, thrombin generation, P-selectin expression, soluble CD40L, and inflammation marker release are some of the consequences of effective P2Y 12 blockage [2,5]. Several drugs targeting the P2Y 12 receptor have been developed, like the thienopyridines ticlopidine, clopidogrel, and prasugrel that selectively and irreversibly inhibit the P2Y 12 receptor.…”
Section: P2y12 Receptor Inhibitorsmentioning
confidence: 99%